Mechanical and Fracture Characterization of Epoxy/PLA/Graphene/SiO2 Composites (Fracture and Structural Integrity, 2023)
This work investigated the effects of graphene and SiO2 addition on the mechanical and fracture properties of epoxy (80%) - Polylactic acid (PLA) (20 %) composites. Epoxy-PLA composites were loaded with graphene and SiO2 (0.1-0.5 wt. % with equal weightage of each filler), and were manufactured by bath sonication followed by manual casting.  The tensile, flexural strength and fracture toughness of nanocomposites increased with an increase in filler concentration till it reached 0.3 wt. %. The addition of filler content higher than 0.3 wt. % drastically reduced the mechanical and fracture properties. The fractured surfaces from the tensile tests were examined using Scanning electron microscopy imaging to understand the effects of filler addition. The numerical analysis was also performed to simulate the impact of filler concentration on the tensile strength of nanocomposites using representative volume element (RVE) in ANSYS workbench.
Keywords: SEM; Mechanical Properties; Polymer composites; Fracture